Role of Sea Surface Microlayer Properties in Cloud Formation - Hendrickson, Brianna N.; Brooks, Sarah D.; Thornton, Daniel C. O.; Moore, Richard H.; Crosbie, Ewan; Ziemba, Luke D.; Carlson, Craig A.; Baetge, Nicholas; Mirrielees, Jessica A.; Alsante, Alyssa N. (Frontiers in Marine Science, 2021)
To date, the relative contribution of primary marine organic matter to the subset of atmospheric particles that nucleate cloud droplets is highly uncertain. Here, cloud condensation nuclei (CCN) measurements were conducted on aerosolized sea surface microlayer (SML) samples collected from the North Atlantic Ocean during the NASA North Atlantic Aerosols and Marine Ecosystems Study (NAAMES), κ values were predicted for three representative high molecular weight (HMW) organic components of marine aerosol: 6-glucose, humic acid, and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). The predicted κ values for pure organic aerosols varied by only ±0.01 across all of the organics chosen. For the desalted SML samples, calculations assuming an organic composition of entirely RuBisCO provided the closest predicted κ values for the desalted SML samples with a mean κ value of 0.53±0.10. These results indicate that it is the sea salt in the SML which drives the cloud formation potential of marine aerosols. While the presence of organic material from the ocean surface waters may increase aerosol mass due to enrichment processes, cloud formation potential of mixed organic/salt primary marine aerosols will be slightly weakened or unchanged compared to sea spray aerosol.